Anthracyclines and ellipticines as DNA-damaging anticancer drugs: recent advances - Kizek, Rene; Adam, Vojtech; Hrabeta, Jan; Eckschlager, Tomas; Smutny, Svatopluk; Burda, Jaroslav V; Frei, Eva; Stiborova, Marie (Pharmacology & therapeutics, 2012)
Over the past forty years, anthracyclines and ellipticines have attracted attention as promising cytostatics. In this review, we focus on their mechanisms of cytoxicity, DNA-damaging effects and adverse side-effects. We also summarize ways to enhance the therapeutic effects of these drugs together with a decrease in their adverse effects. Current drug design strategies are focused on drug bioavailability and their tissue targeting, whereas drug delivery to specific intracellular compartments is rarely addressed. Therefore, therapies utilizing the antineoplastic activities of anthracyclines and ellipticines combined with novel strategies such as nanotechnologies for safer drug delivery, as well as strategies based on gene therapy, could significantly contribute to medical practice.
Keywords: reaktivní formy kyslíku; Anthracyclines; Nanoparticles; Humans; Drug Carriers; elipticiny; Antineoplastic Agents; lidé; zvířata; Reactive Oxygen Species; antracykliny; Neoplasms; nanočástice; nosiče léků; protinádorové látky; nádory; poškození DNA; DNA Damage; Animals; Ellipticines; adukty DNA; DNA Adducts